Photocatalytic removal of methylene blue using immobilized transition metals doped titanium dioxide on glass and granular activated carbon - Kang, Ling Bao (2009)
Photocatalytic degradation of methylene blue (MB) dye in aqueous solution using metal-doped titania (TiO2) under UV-A light and in the presence of H2O2 were investigated The photocatalysts used were single metal-doped TiO2 (i.e. Cr3+-TiO2, Cu2+-TiO2, Fe3+-TiO2, Mo5+-TiO2, and V5+-TiO2) and dual metal-doped TiO2 (i.e. Cr3+,Mo5+-TiO2, Cr3+,V5+-TiO2, Cu2+,Mo5+-TiO2, Cu2+,V5+-TiO2, Fe3+,Mo5+-TiO2 and Fe3+,V5+-TiO2) coated on Pyrex-glass tubes, and single metal doped-TiO2 (i.e. V5+- TiO2) coated on granular activated carbon (GAC). All the catalysts were prepared in the lab and the doping/coating was done according to sol-gel dip-coating method. For comparison, undoped TiO2 coated on Pyrex-glass tube and GAC were also studied. The reactions were carried out in a photo-reactor. Subsamples of the dye solution was withdrawn at specific time intervals and its absorbance was measured at λmax= 665 nm using a UV-Vis spectrophotometer. The resultant dye degradation was presented as % dye removed and comparisons were made for its values at 120 minutes. The results showed that the degradation of MB using these titaniaassisted systems increased with reaction time. Equilibrium, however, was not attained within 120 minutes. Amongst the single metal-doped TiO2 systems only V5+-TiO2 produced greater degradation of MB compared with the undoped TiO2. The other single metal-doped TiO2 systems (Mo5+-TiO2> Fe3+-TiO2≈ Cr3+-TiO2≈ Cu2+-TiO2) produced much lower degradation compared to undoped TiO2. For dual metal-doped TiO2 systems, the degradation efficiency followed the order: Cu2+,V5+- TiO2> Fe3+,V5+-TiO2> Cr3+,V5+-TiO2> Cr3+,Mo5+-TiO2≈ Fe3+,Mo5+-TiO2≈ Cu2+,Mo5+- TiO2. Only Cu2+,V5+-TiO2 produced greater degradation of MB compared with the undoped TiO2. However, it’s efficiency was lower than V5+-TiO2 but higher than Cu2+-TiO2. Meanwhile the V5+-doped and undoped TiO2 catalysts coated on GAC did not exhibit significant photoactivity. The removal of MB from solution by both systems was of similar magnitude to that of due to adsorption by GAC and was about 2x less efficient compared with V5+-TiO2 and TiO2 coated on Pyrex-glass tubes. All the above reactions fitted well with pseudo-first-order kinetics according to the Langmuir-Hinshelwood model. Overall, among the systems investigated, photocatalytic degradation of MB is most efficient when V5+-doped TiO2 coated on an inert support, namely Pyrex-glass tubes, was used.